2023
DOI: 10.3390/biom13020296
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Quorum-Sensing Peptides as Immune Modulators Present in Systemic Circulation

Abstract: Quorum-sensing peptides (QSPs) are bacterial peptides traditionally considered only as inter-bacterial communication molecules. Recently, their involvement in microbiome–host interactions influencing host diseases such as cancer and sarcopenia were explored. However, it is still unknown to what extent these peptides have the potential to modulate the immune system. In this proof-of-concept study, we screened 89 QSPs for their potential to induce IL-6 and TNFα in murine splenocytes and J774 macrophages. Confirm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…This screen identified several peptides that induced a significant immune response, including hits from Staphylococcus aureus , Staphylococcus epidermidis , Bacillus cereus , Bacillus thuringiensis , and Enterococcus faecalis . This study also identified the Bacillus peptide pheromone PapR71 in human plasma, indicating that bacterial signaling peptides with immunomodulatory activity may be biologically relevant in the host context ( De Spiegeleer et al., 2023 ). The evaluation of bacterial peptides traditionally associated with quorum sensing for their ability to induce host immune responses therefore represents an interesting approach for identifying new ways by which bacteria modulate their host environment.…”
Section: Discussionmentioning
confidence: 83%
“…This screen identified several peptides that induced a significant immune response, including hits from Staphylococcus aureus , Staphylococcus epidermidis , Bacillus cereus , Bacillus thuringiensis , and Enterococcus faecalis . This study also identified the Bacillus peptide pheromone PapR71 in human plasma, indicating that bacterial signaling peptides with immunomodulatory activity may be biologically relevant in the host context ( De Spiegeleer et al., 2023 ). The evaluation of bacterial peptides traditionally associated with quorum sensing for their ability to induce host immune responses therefore represents an interesting approach for identifying new ways by which bacteria modulate their host environment.…”
Section: Discussionmentioning
confidence: 83%
“…The even more interesting aspect that emerged from the explorative data is that for certain of these peptides, the inflammatory effect would be age-dependent. Moreover, for a biologically relevant microbiome-host immune system interaction, a role of primary importance would hypothetically refer to QSPs produced by skin bacteria such as staphylococcal species [176].…”
Section: Cutaneous Microbiome As a Specific Pattern Of Frailtymentioning
confidence: 99%